The Effect of Resistance Band on Arm Muscle Strength in Overhead Service Training in Citra Club Volleyball Players - Fauzi Hermana; Encep Sudirjo; Dewi Susilawati (Tadulako Journal Sport Sciences And Physical Education, 2026)
The overhead serve is an important technique in volleyball that initiates attacks and creates scoring opportunities. The effectiveness of this technique is influenced by several physical factors, particularly upper-limb muscle strength. Resistance band training was selected for this study because it provides elastic resistance, allowing more flexible, safe, and sport-specific movement patterns than many conventional strength-training methods, making it suitable for youth athletes. This study aimed to examine the effect of overhead serve training using resistance-band media on arm muscle strength in volleyball players at Citra Club. This research employed a quantitative, pre-experimental design with a one-group pretest–posttest. The sample consisted of 16 volleyball players aged 10–18 years, selected purposively. Arm muscle strength was measured using a handgrip dynamometer as an indicator of general upper-limb muscular strength during physical fitness assessment. The training program consisted of 10 sessions over five weeks. The results showed that the average arm muscle strength increased from the pretest to the posttest. The normality test using the Normal Probability–Probability Plot (P–P Plot) indicated that the residuals were normally distributed, as the points followed a diagonal pattern. In addition, the Normalized Gain (N-Gain) analysis yielded an average value of 0.0604, indicating that the training program produced a moderate improvement in players' arm muscle strength. These findings indicate that overhead serve training using resistance band media can improve arm muscle strength in youth volleyball athletes and can serve as an alternative training method in volleyball coaching programs.